2010
DOI: 10.1002/lary.20887
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of salvage and planned pharyngolaryngectomy with jejunal transfer for hypopharyngeal carcinoma after chemoradiotherapy

Abstract: Salvage pharyngolaryngectomy and jejunal transfer can be performed safely and reliably for patients with locally recurrent hypopharyngeal carcinoma, and it is an excellent option after a failure of definitive chemoradiotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 23 publications
4
28
2
Order By: Relevance
“…In addition, the thick mesentery can provide good coverage to support skin grafting in cases in which primary closure of neck skin is not possible (see Figure 4). 6,7,[22][23][24][26][27][28] Good swallowing function was achieved in our series. With respect to fistula formation, the rates of occurrence according to previous reports were 0%-30%, 6,7,22-28 as compared with 3.7% in our cases.…”
Section: Discussionsupporting
confidence: 58%
“…In addition, the thick mesentery can provide good coverage to support skin grafting in cases in which primary closure of neck skin is not possible (see Figure 4). 6,7,[22][23][24][26][27][28] Good swallowing function was achieved in our series. With respect to fistula formation, the rates of occurrence according to previous reports were 0%-30%, 6,7,22-28 as compared with 3.7% in our cases.…”
Section: Discussionsupporting
confidence: 58%
“…Kadota et al reported the results of an analysis on 14 patients who underwent salvage surgery after definitive chemoradiotherapy in a single-institution study. The 5-year disease-free survival and local control rates were 57.1% and 92.9%, respectively [20]. However, less favorable results have also been reported.…”
Section: Discussionmentioning
confidence: 98%
“…Currently, fasciocutaneous free flaps, in particular radial forearm (RF) and anterolateral thigh (ALT), are considered among the main options for such a reconstructive purpose, especially considering the high rates of PCF and stenosis generally observed after pectoralis major myocutaneous (PMMC) pedicled flap, and the non‐negligible complication rate associated with a jejunum free flap …”
Section: Introductionmentioning
confidence: 99%